Monetary and Macroprudential Policy Rules in a Model with House Price Booms - Scott, Alasdair (IMF Working Papers; Working Paper ;, 2009)
We argue that a stronger emphasis on macrofinancial risk could provide stabilization benefits. Simulations results suggest that strong monetary reactions to accelerator mechanisms that push up credit growth and asset prices could help macroeconomic stability. In addition, using a macroprudential instrument designed specifically to dampen credit market cycles would also be useful. But invariant and rigid policy responses raise the risk of policy errors that could lower, not raise, macroeconomic stability. Hence, discretion would be required.